Pulsed Electromagnetic Field Affects the Development of Postmenopausal Osteoporotic Women with Vertebral Fractures - Liu, Wei (Biomed Res Int, 2021)
BACKGROUND: Postoperative pain, dysfunction, and significant bone loss may occur after vertebral fractures, which will lead to the occurrence of refractures and shorten the survival time, so postoperative rehabilitation is very important. Pulsed electromagnetic field therapy is noninvasive, pain-relieving, and beneficial to reduce bone loss and is an important treatment for patients to recover after surgery. Therefore, this study analyzed the effect of postmenopausal women's vertebral fracture rehabilitation after pulsed electromagnetic field treatment. METHOD: This study uses a randomized controlled study, respectively, in the pulsed electromagnetic field treatment group (40 cases) and the control group (42 cases), respectively. We studied the results of health-related quality of life scores (HRQOL), back pain, body function, hip bone density, bone microstructure of tibia, and radius after 1 month and 3 months after surgery. RESULTS: Compared with the control group, the pulsed electromagnetic field treatment group (PEMF) can improve significantly the psychological score, 6-minute walk test, and Chair Sit-and-Reach one month after the operation. And at 3 months after surgery, the pulsed electromagnetic field treatment group can improve significantly in health-related quality of life scores (HRQOL), back pain, and body function. Regarding the effect of changes in bone mass, compared with the control group, pulsed electromagnetic field treatment had no significant effect on changes in hip bone density. As a result of changes in bone microstructure, pulsed electromagnetic field treatment can significantly improve the bone microstructure of the radius and tibia three months after vertebral fractures. CONCLUSION: Pulsed electromagnetic field therapy has positive significance for improving pain, body functional changes, and bone loss after vertebral fracture surgery.